The impact of hotel staff appraisal to career development - Putu Elsa Oktavia Dewi; I Ketut Astawa; Ni Made Ernawati; I Ketut Suarta (Politeknik Negeri Bali, 2019)
The purpose of this research is to analyze the impact of staff appraisal to the employee career development and how to manage employee career development at a 5-star hotel ini Nusa Dua, Bali. The data used in this research are quantitative data and qualitative data obtained from passive participation observations, obviously or disguised observations, interview, documentation, literature review, and secondary data named Performance Management Objectives. After obtaining the data then tested the validity test and reliability test used SPSS 17. From the 391 employees were taken 198 samples respondents (hotel employees) using Slovin method. The data analysis technique used is Descriptive Statistics Analysis and Qualitative Descriptive Analysis. The results reveal that staff appraisal gave a positive impact to the employee career development. It is because the staff appraisal assists in employee career development and it can be used by the employees as a reference of their performance. Thus, the staff appraisal using Performance Management Objectives has an impact on employee career development through the promotion process which is 12 employees of the hotel are doing promotion in 2019.